(untitled) (Tamaddun, 2025)
This study explores how Arabic-speaking academic colleagues exchanged Ramadan greetings on WhatsApp during Ramadan 2025. A total of 56 messages were collected and examined using qualitative content analysis. The focus was on the language used and the social purposes behind these greetings. Common phrases such as ‘Ramadan Kareem’ and ‘Ramadan Mubarak’ were frequently used, serving not just as polite expressions but as meaningful speech acts that helped build social bonds and express shared cultural and religious values. The study also looked at the emojis that often accompanied the greetings such as crescent moons, praying hands and hearts which added layers of politeness, unity and spiritual sentiment. The findings show how WhatsApp allows people to adapt traditional greetings into shorter, more modern formats, helping to maintain cultural traditions even in professional digital spaces. This research adds to our understanding of digital communication and shows how language use is shaped by culture and context in mobile messaging among Arabic-speaking professionals